The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acssuschemeng.9b02781
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Improving the Protein Yield in pH-Shift Processing of Ulva lactuca Linnaeus: Effects of Ulvan Lyases, pH-Exposure Time, and Temperature

Abstract: Globally, there is a need for novel vegetarian protein sources. We recently showed that the pH-shift process, using alkaline protein solubilization followed by isoelectric precipitation, is an efficient way to produce extracts with high protein concentrations from Ulva lactuca (>50% on a dry matter basis). However, the total protein yield was low, and to improve this, the effects of adding ulvan lyase, preincubating the seaweed homogenate at pH 8.5 and using different protein extraction temperatures (8 °C, RT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
3
15
0
Order By: Relevance
“…Robin et al (2018) also did a mechanical extraction, but combined with pulsed electric field and with dialysis for protein purification, achieving a total protein yield of 2.9% (Robin et al 2018). The precipitation yield obtained in this current study was within the range of what have been achieved in other studies (Harrysson et al 2018;Harrysson et al 2019). Harryson et al (2019 demonstrated improved extraction yields and a total protein yield of 29% of total biomass protein using a pH-shift method, that includes step-wise incubation of homogenized Ulva at pH 8.5 and pH 12, and adding a freezing step during the precipitation (Harrysson et al 2019).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Robin et al (2018) also did a mechanical extraction, but combined with pulsed electric field and with dialysis for protein purification, achieving a total protein yield of 2.9% (Robin et al 2018). The precipitation yield obtained in this current study was within the range of what have been achieved in other studies (Harrysson et al 2018;Harrysson et al 2019). Harryson et al (2019 demonstrated improved extraction yields and a total protein yield of 29% of total biomass protein using a pH-shift method, that includes step-wise incubation of homogenized Ulva at pH 8.5 and pH 12, and adding a freezing step during the precipitation (Harrysson et al 2019).…”
Section: Discussionsupporting
confidence: 78%
“…So far, protein extraction from seaweeds has primarily been performed by osmotic shock, often combined with either alkaline extraction or pulsed electric field, using either dried and milled biomass or fresh grinded biomass (Harrysson et al 2019;Vilg and Undeland 2017;Kazir et al 2019;Maehre et al 2016;Postma et al 2018;Kadam et al 2017;Bleakley and Hayes 2017). Alkaline processing have for other proteins shown to induce amino acid racemization, resulting in decreased protein digestibility (Schwass and Finley 1984;Hayashi and Kameda 1980;Friedman 2004), why the aim of this study was to test a mechanical extraction technique, adding antioxidant during extraction to improve protein quality.…”
Section: Introductionmentioning
confidence: 99%
“…is a candidate raw biomass with a high growth rate and high protein, lipid, carbohydrate yield suitable for food application ( Kazir et al, 2019 , Khairy and El-Shafay, 2013 ). A recent study showed that pH-shift of Ulva sp improves the nutrient contents and gives a high grade of food applications ( Harrysson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that ocean acidification of Ulva sp. improves the protein yield to 29% by 2.3-fold higher than recorded by control and gives a high grade of food applications ( Harrysson et al, 2019 ). Gao et al, (2017) reported that protein levels were increased in U. rigida in response to pH-shifting.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when compared to the amount of soybean intake to reach the EAA recommendations (170 g dw, based on average soybean AA profile from Brazil, China, and the US) (Grieshop and Fahey, 2001), seaweeds should be considered an interesting future protein source. Furthermore, recent studies on Ulva show that its proteins can be concentrated by different extraction processes (Harrysson et al, 2019;Trigo et al, 2021;Juul et al, 2022), in a similar manner as is currently done with soy, which further enhances the prospects of U. fenestrata biomass as a protein source for human consumption.…”
Section: Proteins and Amino Acidsmentioning
confidence: 98%